Pharmacokinetic and Pharmacodynamic Comparison of Once‐Daily Efavirenz (400 mg vs. 600 mg) in Treatment‐Naïve HIV‐Infected Patients: Results of the ENCORE1 Study. Issue 4 (14th July 2015) - Dickinson, L; Amin, J; Else, L; Boffito, M; Egan, D; Owen, A; Khoo, S; Back, D; Orrell, C; Clarke, A; Losso, M; Phanuphak, P; et al.
Abstract : Daily efavirenz 400 mg (EFV400) was virologically noninferior to 600 mg (EFV600) at 48 weeks in treatment‐naïve patients. We evaluated EFV400 and EFV600 pharmacokinetics (NONMEM v. 7.2), assessing patient demographics and genetic polymorphisms ( CYP2B6, CYP2A6, CYP3A4, NR1I3 ) as covariates and explored relationships with efficacy (plasma HIV‐RNA (pVL) <200 copies/mL) and safety outcomes at 48 weeks in 606 randomized ENCORE1 patients (female = 32%, African = 37%, Asian = 33%; EFV400 = 311, EFV600 = 295). CYP2B6 516G>T/983T>C/ CYP2A6 *9B/*17 and weight were associated with efavirenz CL/F. Exposure was significantly lower for EFV400 (geometric mean ratio, GMR; 90% confidence interval, CI: 0.73 (0.68–0.78)) but 97% (EFV400) and 98% (EFV600) of evaluable pVL was <200 copies/mL at 48 weeks ( P = 0.802). Four of 20 patients with mid‐dose concentrations <1.0 mg/L had pVL ≥200 copies/mL (EFV400 = 1; EFV600 = 3). Efavirenz exposure was similar between those with and without efavirenz‐related side effects (GMR; 90% CI: 0.95 (0.88–1.02)). HIV suppression was comparable between doses despite significantly lower EFV400 exposure. Comprehensive evaluation of efavirenz pharmacokinetics/pharmacodynamics revealed important limitations in the accepted threshold concentration.